The arts and the social determinants of health: findings from an inquiry conducted by the United Kingdom All-Party Parliamentary Group on Arts, Health and Wellbeing. Issue 1 (2nd January 2020) - Gordon-Nesbitt, Rebecca; Howarth, Alan
ABSTRACT: Background : The United Kingdom All-Party Parliamentary Group on Arts, Health and Wellbeing was formed in 2014 and, the following year, initiated an Inquiry into the relationship between arts engagement, health and wellbeing. This led to a substantial report being launched in Parliament in July 2017. Methods : The Inquiry comprised 16 round-table discussions, a series of expert meetings and a lengthy period of desk-based research. The latter applied a realist method in seeking to reconcile policy, practice and evidence. Consideration of the social determinants of health formed the theoretical framework. Results : Evidence was found of a beneficial relationship between arts engagement, health and wellbeing across the life course. Conclusions : Arts engagement can mitigate the social determinants of health by influencing perinatal mental health and child cognitive development; shaping educational and employment opportunities and compensating for work-related stress; building individual resilience and enhancing communities. Further research is needed in this area.